2019
DOI: 10.1101/599399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imbalance in the response of pre- and post-synaptic components to amyloidopathy

Abstract: Alzheimer's disease (AD)-associated synaptic dysfunction drives the progression of pathology from its earliest stages. Aβ species, both soluble and in plaque deposits, have been causally related to the progressive, structural and functional impairments observed in AD. It is, however, still unclear how Aβ plaques develop over time and how they progressively affect local synapse density and turnover. Here we observed, in a mouse model of AD, that Aβ plaques grow faster in the earlier stages of the disease and if… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Surprisingly, we found that presynaptic structures harboring VGluT1 are reduced in the visual cortex of hAPP mice. This finding is consistent with a recent study showing reduced bouton density but unaltered postsynaptic spine density in the barrel cortex of the same mouse model [93]. Furthermore, .…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, we found that presynaptic structures harboring VGluT1 are reduced in the visual cortex of hAPP mice. This finding is consistent with a recent study showing reduced bouton density but unaltered postsynaptic spine density in the barrel cortex of the same mouse model [93]. Furthermore, .…”
Section: Discussionsupporting
confidence: 93%
“…Images were taken on Leica SP8 3 × STED Confocal and processed with ImageJ. In some instances (Supplemental Figure S6B) brain tissue was subjected to clearing with X‐Clarity technology (Logos Biosystems) as described in 32 . Images for 3D reconstruction were acquired on Nikon A1R HD Upright Multi‐Photon/Confocal microscope.…”
Section: Methodsmentioning
confidence: 99%